UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA DILIHAT DARI PASAL 18 B AYAT 2 UUD 1945 - Hanif Nurcholis (Masalah-Masalah Hukum, 2014)
The status of Village has still been outside of the government bureucratic-system. It is still being positioned as a community that regulated by State and given the governmental tasks. The Law Number